Analisis Geometrik Jalan Raya dengan Pendekatan Bina Marga (Studi Kasus : Jl. Poros Tikungan SP 4, Kelurahan Makbalim, Kilometer 37, Kabupaten Sorong) - Setiawan, Ahmad Ardi; S, Muh. Rizal; Repmi Tamsih, Intan Java Turis (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2025)
The purpose of road geometry planning is to produce safe infrastructure and the maximum efficiency of traffic flow services. It can maximize the ratio of the level of use of the implementation cost on the road. The condition of Jalan Poros, Bend SP 4, Sorong Regency is a straight road and there are several steep and sharp bends, so it becomes one of the factors for accidents. Slippery road conditions are also often a factor in accidents for two-wheeled users. The purpose of this study is to analyze and describe the condition of the road geometry and also to evaluate the horizontal curve (bend) on the SP 4 bend axis road section and whether it is appropriate based on the 2020 Bina Marga Guidelines. The research method used is quantitative research. The primary data used in this study are road geometric data, environmental conditions, topographic maps, road width, and curve length. The secondary data are plan speed data, bend coordinate data, and plan drawings. The value of e in calculating the distribution curve coefficient f and e gives a value of 8.75%, while the value of Lc (calculating the length of the transition curve) = 207.07 m. The requirement for the spiral-circle-spiral curve is Lc ≥ 20m so this curve can be designed as a spiral-circle-spiral curve. The SP 4 bend in Sorong Regency has a flat terrain type. Based on calculations, the value of Lc = 206.893 and the value of Ls = 29.76. Both values are more than 20m, so they meet the requirements of a type bend.